EKSPERIMENTASI MODEL PEMBELAJARAN TAPPS DAN PS PADA MATERI STATISTIKA DITINJAU DARI KREATIVITAS BELAJAR MATEMATIKA SISWA KELAS XI IPS - Arianto, Febri; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2016)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from the studentsâ Mathematics learning creativity. The learning models compared were Thinking Aloud Pair Problem Solving (TAPPS), Problem Solving (PS), and direct learning. This study was quasi-experimental research. The population of this study was students in grade XI social class of state senior high schools in Klaten year 2015/2016. Stratified cluster random sampling was utilized for collecting samples. Two ways Anova with 3x3 of factorial design was used for hypothesis test. Based on the analysis, it can be concluded: (1) the students who are given TAPPS have better achievement than those who are given PS and direct learning, students who are given PS have the same achievement as those who are given direct learning, (2) high creativity students have better achievement than middle and low creativity students, middle creativity students have the same achievement as low creativity students, (3) in the TAPPS; high, middle, and low creativity students have the same achievement. In the PS; high, middle, and low creativity students have the same achievement. In direct learning, high creativity students have the same achievement as middle creativity students, middle creativity students have the same achievement as low creativity students. High creativity students have better achievement than low creativity students, (4) in high creativity, the students who are given TAPPS have the same achievement as those who are given PS and direct learning. In the middle creativity, those students who given TAPPS have the same achievement as those who are given PS and direct learning. In low creativity, the students who are given TAPPS have the same achievement as those who are given PS; those who are given PS have the same achievement as those who are given direct learning model, while the students who are given TAPPS have better achievement than those who given direct learning.Key words: TAPPS, PS, Direct learning, Mathematics Learning Creativity